تأثيربعض المستخلصات النباتية المائية والمركبات الكيمياوية المثبطة لأنزيم اليوريز في خفض تطاير الامونيا من اليوريا المضافة حقليا لترب اهوار ذي قار - الأنصاري عبد الميدي صالح (University of Thi-Qar Journal of Science, 2014)
The present study was inducted to show the effect of aqueous plant extracts and chemical compounds thiosulphate ammonium (ATS) and hydroqenone (HQ)upon Ammonia volatilization which added 10% .20% respaicvtily from urea weight after 40 days of fertilizer adding .accoding to close system. The results were appeared significantly reduction at 0.01 level volatilization ammonia quantity for urea treated with the extract of Eucalyptus camaldulensrs Dehn L. , Myrtus communis L, Phoenix dactlifera L, Oryza sativa, Cynodon dactylon L.Pers HQ and ATS30.320, 32.045, 26.761, 29.643, 29.980, 32.061 and 31.165 Kg NH3 Ha-1 compared with the control treatment that was 36.633kg NH3 Ha-1 .All treatments of the plant extracts were significantly difference with (HQ and ATS) treatments and with themselves at level probably (0.01) except MYrtus communis L. treatment was not significantly difference with HQ treatment extract ,An amount of ammonia volatilization increased significantly when increased the levels of Nitrogen (100,200,and 300)kg N Ha-1 were (24.485 , 31.670, and 37.075) kg NH3 Ha-1 to all levels respectively .The rates for active amount of ammonia volatilization to all time periods (2 ,5 ,7,10, 15,20,30,and 40)days were (2.375 ,3.077,3.37 ,4.964 , 5.188 ,5.841,3.825 and 2.269)kg NH3Ha-1 respectively . At last the results showed a significantly differences at active ammonia volatilization at levels probably (0.01) .